Salvianolate injection for hypertensive nephropathy patients who were using valsartan: A systematic review and meta-analysis - Xu, Qiyao; Shen, Yuehong; Zhao, Jianqiao; Shen, Jianping (Frontiers in Pharmacology, 2023)
Background: The treatment of hypertensive nephropathy has remained unchanged for many years. Salvianolate is the main active component extracted from Salvia Miltiorrhiza. The current studies seem to suggest that salvianolate has a certain therapeutic effect on hypertensive nephropathy. Objective: The purpose of this meta-analysis is to evaluate the effect and safety of salvianolate on hypertensive nephropathy under the condition of standardized use of valsartan. Methods: We conducted a systematic search (unlimited initial date to October 22, 2022) in PubMed, Web of Science, the Cochrane Library, Embase, China National Knowledge Infrastructure, Wanfang Data knowledge service platform, China Science and Technology Journal Database, China Biomedical Literature Service System. Searching for the study of salvianolate on hypertensive nephropathy. Two reviewers independently included the study that met the inclusion criteria, and extracted data, evaluated the quality of the study. We use RevMan5.4 and stata15 software for this meta-analysis. We use GRADEprofiler 3.2.2 software for evidence quality assessment. Results: This meta-analysis included seven studies (525 patients). Compared with the use of valsartan combined with conventional treatment, salvianolate combined with valsartan and conventional treatment can further improve the efficacy (RR=1.28, 95%CI:1.17 to 1.39), reduce blood pressure [systolic blood pressure (MD=8.98, 95%CI:-12.38 to -5.59); diastolic blood pressure (MD=5.74, 95%CI:-7.20 to -4.29)], serum creatinine (MD=-17.32, 95%CI:-20.55 to -14.10), blood urea nitrogen (MD=-1.89, 95%CI:-3.76 to -0.01), urine microalbumin (MD=-23.90, 95%CI:-26.54 to -21.26), and urinary protein to creatinine ratio (MD=-1.92, 95%CI:-2.15 to -1.69), cystatin C (MD=-1.04, 95%CI:-1.63 to -0.45,) and increase calcitonin gene-related peptide (MD=18.68, 95%CI:12.89 to 24.46) without increasing adverse reactions (RR=2.20, 95%CI:0.52 to 9.40). But it has no additional effect on endothelin-1 and malondialdehyde. The quality of evidence ranged from moderate to very low. Conclusion: This meta-analysis shows that the salvianolate can further improve renal function of hypertensive nephropathy patients based on valsartan was used. Therefore, salvianolate can be used as a clinical supplement for hypertensive nephropathy. However, the quality of the evidence is not high due to the uneven quality of the included studies and the insufficient sample size, we still need a lot of large sample size studies with more perfect design to confirm these results.